Ethical appraisal of the relationship between christian virtues and entrepreneurial development in Nigeria (2020)
This paper underscores the importance of Christian ethical virtues in entrepreneurial development in Nigeria and how it can be of immense benefit to individual and the nation at large. Entrepreneurship which is the process of doing something new and something different for the purpose of creating wealth for the individual and adding value to society has not been having its fair share in the recent time and this was not the case in the past. The country was rated among one of the most developed economies in the world with its triplistic economy as the 12th largest crude oil producer in the world, 9th most populous country of the world and second largest economy in Africa with earnings of an estimated $2.2 million a day in oil revenue. But, in spite of these giant strides, Nigeria is still ranked among the poorest nations in the world in recent time. Its failure as a nation is attributable to many factors which includes corruption, bad governance, ineptitude, lack of managerial skills, government policies and dilapidated infrastructures. Existing studies so far carried out on entrepreneurship in Nigeria have focused mainly on the social, economic, psychological and the influence of politics in business with little attention given to the Christian ethical virtues that are germane to entrepreneurial development in this period of economic meltdown which has negatively affected the growth of the country thereby making her to take a back seat among the developed economies. There is no doubt denying the fact that entrepreneurs in Nigeria have displayed herculean task and great exploits in revamping the economy, but, their failure to imbibe the Christian virtues of prudence, justice, courage, temperament, self-discipline, diligence, resourcefulness and perseverance that are necessary for entrepreneurial development has made such exploit to experience a stunted economic growth and malnourished economic development. Therefore, this paper has examined the state of entrepreneurship in Nigeria, factors responsible for entrepreneurial failure, and how Christian ethical values can be used to address such failure. Recommendation will also be made where necessary.